Acute treatment of myasthenia gravis with intranasal neostigmine: clinical and electromyographic evaluation. Issue 12 (December 1991) - Ricciardi, R; Rossi, B; Nicora, M; Sghirlanzoni, A; Muratorio, A
Abstract : The effectiveness of intranasal neostigmine (9.3-13.8 mg) was tested in 20 subjects with myasthenia gravis, classified as Osserman grades 2A and 2B. In all cases the drug produced significant clinical and electromyographic improvement. No side effects were reported during the treatment.